2015
DOI: 10.17265/1934-7375/2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Materials for the Separation of Germanium from Gallium, Zinc and Cobalt

Abstract: Abstract:In the past 68 Ge (Germanium-68) was purified with toxic organic solvents in liquid-liquid extractions making the product unacceptable by the FDA (food and drug Administration) for human use. The authors report initial studies utilizing three or four columns consisting of sequences of AG1, AG50, Chelex 100 and/or Sephadex G25 resins. Five purification methods were examined and a separation consisting of the sequence: AG1-Chelex100-Sephedex G25 provided 87% recovery of germanium. Fractionation of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The studies indicated very high germanium concentrations could be obtained, but cobalt retention on Sephadex © G25 was identical to germanium (Fitzsimmons and Mausner, 2015a). This approach would require 4-5 columns to purify 68 Ge that meet specifications.…”
Section: Introductionmentioning
confidence: 99%
“…The studies indicated very high germanium concentrations could be obtained, but cobalt retention on Sephadex © G25 was identical to germanium (Fitzsimmons and Mausner, 2015a). This approach would require 4-5 columns to purify 68 Ge that meet specifications.…”
Section: Introductionmentioning
confidence: 99%
“…We examined separations chemistry starting after the leaching step. In the initial studies we evaluated the purification of Ge from Co, Ga, and Zn with a three column approach using an alkaline solution [12]. The separations used Sephadex © G25 resin and produced germanium in very high concentrations.…”
mentioning
confidence: 99%